Dissection of closely linked QTLs controlling stigma exsertion rate in rice by substitution mapping - Quanya Tan; Chengshu Wang; Xin Luan; Lingjie Zheng; Yuerong Ni; Weifeng Yang; Zifeng Yang; Haitao Zhu; Ruizhen Zeng; Guifu Liu; Shaokui Wang; Guiquan Zhang (Theoretical and Applied Genetics, 2021)
Key message Through substitution mapping strategy, two pairs of closely linked QTLs controlling stigma exsertion rate were dissected from chromosomes 2 and 3 and the four QTLs were fine mapped. Abstract Stigma exsertion rate (SER) is an important trait affecting the outcrossing ability of male sterility lines in hybrid rice. This complex trait was controlled by multiple QTLs and affected by environment condition. Here, we dissected, respectively, two pairs of tightly linked QTLs for SER on chromosomes 2 and 3 by substitution mapping. On chromosome 2, two linkage QTLs, qSER-2a and qSER-2b , were located in the region of 1288.0 kb, and were, respectively, delimited to the intervals of 234.9 kb and 214.3 kb. On chromosome 3, two QTLs, qSER-3a and qSER-3b , were detected in the region of 3575.5 kb and were narrowed down to 319.1 kb and 637.3 kb, respectively. The additive effects of four QTLs ranged from 7.9 to 9.0%. The epistatic effect produced by the interaction of qSER-2a and qSER-2b was much greater than that of qSER-3a and qSER-3b . The open reading frames were identified within the maximum intervals of qSER-2a , qSER-2b and qSER-3a , respectively. These results revealed that there are potential QTL clusters for SER in the two regions of chromosome 2 and chromosome 3. Fine mapping of the QTLs laid a foundation for cloning of the genes of SER.